EU wine policy in the framework of the CAP: Post-2020 challenges - Eugenio Pomarici; Roberta Sardone (Agricultural and Food Economics, 2020)
The EU Common Agricultural Policy (CAP), and with it the EU wine policy, is experiencing a reform process, started in 2018, in order to address ambitious environmental and social objectives, in conjunction with the goal of a competitive agricultural sector. Given the role of the EU in wine supply, the aim of this paper is to present the design, the rationale and the potential effect of the proposed reform with specific reference to wine sector. To better understand the forthcoming process, it is firstly presented how CAP and its wine policy evolved in terms of objectives and tools over time. The EU wine policy is a paradigmatic example of a combination between the horizontal measures, valid for all agricultural sectors, and vertical measures, peculiarly encompassing the whole wine supply chain. The reform proposal confirms, with some interesting modifications, the set of tools already operating in the sector; however, it calls for a planning of the implementation of the available tools for all products in a unitary frame represented by a national CAP Strategic Plan, applying a lean administrative procedure. In the hypothesis that the COVID-19 outbreak will not cause a radical change in the global agri-food system, the proposed planning process should stimulate shared strategies. These are intended to effectively coordinate, according to the principle of complementarity, the implementation of available policy tools, in order to obtain a better use of resources and a more balanced achievement of all policy objectives.
Keywords: 330; CAP reform; Wine sustainability; CAP Strategic Plan; EU wine sector performance